The rotator cuff tendons of the shoulder joint : anatomy and development of a model to predict and prevent tears - Khong, Chee Houe (2009)
This project aims to develop a finite element model to predict the stress and strain patterns in the rotator cuff. The three dimensional model was constructed from the CT scan images available from the database of Visible Human Project by National Library of Medicine, USA. A software MIMICS was utilized to assemble the CT scan images to reproduce the geometry of the supraspinatus tendon. The geometry was meshed and exported to ANSYS for finite element analysis. The supraspinatus tendon was modeled with viscoelasticity material properties to reflect the actual behavior of the tendon under loading. The simulation results showed that the maximum von-Mises stress occurs at the inferior end of the supraspinatus tendon, and the maximum shear strain occurs at the superior end of supraspinatus tendon. Although the finite element model is able to produce some results, more works is required to validate its results.